A legal study on the offence of infanticide in Malaysia / Mohd Afiq Abdullah ... [et al.] - Abdullah, Mohd Afiq; Amiruddin, Mohd Amirul Idzuan; Ahmad, Mohd Farhan Aliff; Idrus, Mohd Sofian (2011)
The increasing cases of baby dumping which leads to the death of babies attract a lot of attention from the society. Society suggests that the death of the babies caused by their parents should be regarded as murder and the offender should be punished with death sentence. Nevertheless, the current law with regards to killing of a baby by the mother herself is dealt with in Section 309A of the Penal Code which provides the penalty of twenty years of imprisonment provided that the act was done by the mother who was not recovered from the effect of giving birth. Due to the effect of giving birth, the mother would probably suffer from mental disturbance and in consequence she killed her baby. Based on the circumstances mentioned, the mental element on part of the mother is difficult to prove. The question arises as to whether the effect of giving birth affects the mother's ability to think as a normal human being and also the difficulties in determining whether the mother killed her baby under such an effect or not. Thus, this research is done to scrutinize the current law of infanticide under Section 309A of the Penal Code and other relevant sections.